Forests and the future: regional perspectives - Umeh, L.I.; Omoluabi, C.; Salleh, M.N.; Prins, C.; Tomaselli, I.; Abdel Nour, H.O.; Dombeck, M.; Moad, A.; Sayer, Jeffrey A. (2001)
Six brief articles envisage forests and forestry in 2050 in Africa (Umeh; Omoluabi), Asia and the Pacific (Salleh). Europe (Prins), Latin America and the Caribbean (Tomaselli), the Near East (Abdel Nour) and North America (Dombeck; Moad). A final section by Sayer discusses the future management of tropical forests. All the authors concluded that timber harvesting from natural forests will diminish, and these forests will be used increasingly for recreation, conservation and biodiversity.